THE EFFECT OF WORK ETHOS ON PERFORMANCE OF EMPLOYEES IN THE OFFICE OF CULTURE AND TOURISM OF JAYAWIJAYA REGENCY - Haryati, Tati; Ismail, Rudihartono (The International Journal of Accounting and Business Society, 2020)
ABSTRACTPurpose — The purpose of this research is to determine whether there is an effect of the work ethic on the Performance of Employees of the Culture and Tourism Office of Jayawijaya Regency.Design/methodology/approach — The researchers use quantitative research methods with associative to determine the effect of work ethic on employee performance at the Office of Culture and Tourism of Jayawijaya Regency. This research uses library research instruments, observation, documentation, and questionnaires with a Likert Scale.Findings — Results revealed a positive and significant influence between the assessment of Work Ethics and Employee Performance at the Office of Culture and Tourism of Jayawijaya Regency.Practical Implications — The success of an employee's performance can be determined if an agency has a work evaluation system. So an employee must follow the rules and instructions so that later it can be in accordance with the goals of the previous agency.Originality/value — Keywords Work Ethic, Performance, EmployeesPaper Type Research Paper (case study)